2014
DOI: 10.1093/ntr/ntu108
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Smoking Among Tri-Ethnic Daily and Nondaily Smokers

Abstract: introduction: Nondaily smokers experience adverse effects from tobacco use, yet they have been understudied compared to daily smokers. Understanding how reasons for smoking (RS) differ by smoking level, gender, and race/ethnicity could inform tailored interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The study of Berlin et al 17 also points out that women generally smoke more in search of relaxation and also due to social smoking. More recently, in 2014, Pulvers et al 31 , applied the MRSS in 2376 adults smokers and found that the domain of Relaxation/Reduction of Tension had the highest score among women. These findings are relevant and in line with the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Berlin et al 17 also points out that women generally smoke more in search of relaxation and also due to social smoking. More recently, in 2014, Pulvers et al 31 , applied the MRSS in 2376 adults smokers and found that the domain of Relaxation/Reduction of Tension had the highest score among women. These findings are relevant and in line with the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Numerous studies have documented higher rates of nondaily (ie, smoking on only some days) or light smoking (ie, 10 or fewer cigarettes per day [CPD]) among Latinos compared with non-Latino Whites. 15,[18][19][20][21][22] Nondaily smoking is under-studied and undertreated, 22,23 despite its association with significant health risks, [24][25][26][27] making it an important target for study. Additionally, a nuanced analysis demonstrates that significant proportions of Latino smokliefs, and behaviors of one's heritage culture with those of a new culture.…”
Section: Smoking and Acculturation Among Latinos -Pulvers Et Almentioning
confidence: 99%
“…Nondaily smoking is increasingly common among both native and US Latinos 19,38 and is associated with significant health risks, [24][25][26][27] yet is under-studied and under-treated. 22,23 A granular, within smoker analysis among a growing segment of the Latino population that is most at-risk (ie, highly acculturated) stands to make the greatest public health impact. Our study examines variation in the relationship between acculturation and smoking level by sex in order to advance tobacco treatment.…”
Section: Smoking and Acculturation Among Latinos -Pulvers Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified several reasons for ENDS’ increasing popularity among adolescents, including greater visibility in the media 8 , combustible cigarette smoking cessation 9 , interest in flavors 10 , and peer influence 11 . Like other tobacco products 12 , motivations for ENDS use may vary with sociodemographic characteristics. Studies of US adults demonstrate that appealing flavors are more likely to be a reason for use among young adults 13 , and adult women are more likely to report using e-cigarettes because of their use by friends or family members 14 .…”
Section: Introductionmentioning
confidence: 99%